"Effect of floating columns on buildings subjected to seismic forces". Issue 1 (November 2021) - Pawar, Neha; Dabhekar, Kuldeep; Patil, Prakash; Khedikar, Isha; Jaju, Santosh
Abstract: In Recent Trends, buildings are planned to fulfill their architectural and functional requirements but sometimes this creates complexity in its structural strength. One such element is the floating column. It is used to boost Floor Space Index. The Earthquake forces developed at different storey need to be carried down by the shortest path. Discontinuity in the load transfer path leads to poor seismic performance of the structure. Hence as per IS: CODE-1893:2016 clause no-7.1, the Construction of Floating Column is restricted. But there is no limit to research work. The purpose of this research is to analyze the structural irregularity occurring due to floating columns and also to find out the optimized solution to decrease the risk due to earthquake excitation. For Simplicity, the focus of this study is limited to symmetrical G+8 Structure. Finite element Based ETabs software has been used for the analysis. Response spectrum analysis was done in the software. Total ten models are considered with different conditions and their results were compared in terms of Storey displacement, Storey drifts, Base Shear and Overturning moments. All results are compared with the conventional building.